2013
DOI: 10.1002/ejhf.42
|View full text |Cite
|
Sign up to set email alerts
|

The effect of thyroid function on clinical outcome in patients with heart failure

Abstract: Aims Thyroid dysfunction is known to effect cardiac function and is a risk factor for developing heart failure (HF). Data regarding the clinical significance of thyroid‐stimulating hormone (TSH) levels alone as a predictor of outcome in patients with HF is sparse. We evaluated the significance of TSH on clinical outcome in a large cohort of patients with chronic HF. Methods and results Patients with a diagnosis of HF at a Health Maintenance Organization (n = 5599) were followed for cardiac‐related hospitalizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
52
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(57 citation statements)
references
References 37 publications
3
52
0
2
Order By: Relevance
“…11, 12 Thus, cardiac tissue hypothyroidism coexists in HF and may contribute to HF development. Consistent with this theory, recent clinical data 24, 25 found that increased TSH levels (a clinical marker of hypothyroidism) are associated with worse clinical outcome in patients with HF.…”
Section: Discussionmentioning
confidence: 71%
“…11, 12 Thus, cardiac tissue hypothyroidism coexists in HF and may contribute to HF development. Consistent with this theory, recent clinical data 24, 25 found that increased TSH levels (a clinical marker of hypothyroidism) are associated with worse clinical outcome in patients with HF.…”
Section: Discussionmentioning
confidence: 71%
“…As such, reduced fT3 levels may have adverse effects on the cardiovascular system, and thus cause poor prognosis in patients with cardiovascular disease [13,14,16]. Numerous studies have also examined the relationship between TSH levels and outcomes in patients with chronic congestive heart failure [18,20,23]. However, the prognostic value of TSH remains controversial.…”
Section: Discussionmentioning
confidence: 98%
“…Our results do not inform whether thyrotropin levels measured after the clinical onset of cardiovascular disease may have prognostic value, as suggested by some evidence. 60 In addition, we did not examine whether levels of thyroid function tests within the reference ranges may be differentially associated with all-cause mortality 16,61,62 or the risk of non-CHD outcomes, such as atrial fibrillation, 62,63 heart failure, 62 fractures, 64 dementia, 62,65 chronic kidney disease 66 or cancer mortality, 61 as suggested in some prospective studies. However, except for a modestly increased risk of chronic kidney disease, 66 these studies did not show increased disease risk among people with thyrotropin levels in the upper part of the reference range and thus do not provide evidence in support of lowering the upper thyrotropin reference limit.…”
Section: Discussionmentioning
confidence: 99%